Perceived returns to job search - Adams-Prassl, A; Boneva, T; Golin, M; Rauh, C (Elsevier, 2022)
This paper provides new evidence on workers’ perceptions of the returns to job search effort using hypothetical vignettes. This allows us to overcome limitations with survey data on realized behavior in which search effort and reservation wages may be endogenous to perceived job finding rates. The perceived job finding probability is nearly linear in hours searched and only slightly concave for most respondents. While workers are over-optimistic about the probability of receiving a job offer conditional on any search, they perceive the marginal return to additional search hours as positive but comparably low. Job seekers receiving an offer, update their perceived returns upwards, while the beliefs of unsuccessful searchers regress towards the direction of the mean. We find little evidence that novel aspects of the pandemic recession have fundamentally changed workers’ motivations for job search: that an existing job is expected to end or has unsatisfactory pay are the primary motives for on-the-job search. On the contrary, workers’ ability to do their tasks from home is not a strong predictor of job search nor a significant motive for switching occupations.